A method for carbonizing and reactivating construction waste micropowder

By grinding and wet-grinding carbonization activation of construction waste micro powder, the problems of resource utilization of construction waste micro powder and CO2 reduction are solved, and efficient and economical reuse of construction waste and CO2 storage are achieved.

CN116283022BActive Publication Date: 2025-03-28HUBEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310194246.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-03-28
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize construction waste micro powder, and the traditional activation methods consume high energy and large CO2 emissions, which cannot meet the requirements of economical, environmental protection and low energy consumption.

Method used

20-25μm construction waste powder was obtained by grinding and sieving, and mixed with water, sodium citrate and polymer electrolyte water reducing agent for wet grinding. After carbonization is activated, it is used to prepare mortar.

Benefits of technology

It improves the utilization rate of construction waste, enhances the mechanical properties and durability of concrete, and at the same time realizes large-scale emission reduction and resource utilization of CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004106597850000081
    Figure BDA0004106597850000081
  • Figure BDA0004106597850000091
    Figure BDA0004106597850000091
  • Figure BDA0004106597850000092
    Figure BDA0004106597850000092
Patent Text Reader

Abstract

The invention discloses a method for carbonizing and reactivating construction waste micropowder, and belongs to the technical field of building materials. The method for carbonizing and reactivating construction waste micropowder comprises the following steps: mixing 20-25 μm construction waste micropowder with water and adding sodium citrate, and then wet grinding to obtain ultrafine construction waste slurry; mixing the ultrafine construction waste slurry with boric acid and a polymer electrolyte water reducer, and then wet grinding and introducing CO2 for carbonization activation. The carbonized and activated construction waste micropowder is used to prepare mortar, and the mechanical properties and durability are significantly improved. The invention improves the utilization rate of construction waste, and realizes large-scale emission reduction and resource utilization of CO2 while increasing the degree of carbonization and enhancing the performance of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for carbonizing and reactivating building waste micropowder. Background Art

[0002] As an inevitable product of urban renewal, construction waste will continue to be generated in large quantities for a considerable period of time in the future. The construction waste generated by house demolition is 400 million tons per year, and waste concrete accounts for about a quarter of it. The use of traditional treatment methods such as landfill to treat these abandoned construction waste will bring about problems such as waste of land resources, soil pollution, water pollution and air pollution. Research on the recycling and reuse of waste construction waste mainly focuses on recycled aggregates. However, due to the obvious defects of recycled aggregates compared with natural aggregates, further treatment is required, but recycled aggregate concrete is still not as effective as ordinary concrete. In recent years, in order to maximize the removal rate of old mortar on the surface of recycled concrete aggregates, so as to produce higher quality recycled aggregates, many new technologies and equipment have been developed. However, in the recycling process, a large amount of powder waste is still generated, accounting for 20-50% of the total concrete waste. It is worth noting that the recovery of waste cement powder is greatly affected by its source, and the strength and age of waste concrete are the main factors affecting the properties of waste cement powder. The larger the particle size of waste powder during recycling, the higher the porosity and water absorption rate. When it is used in construction fields such as concrete, it will greatly affect the workability, physical and mechanical properties and durability of concrete. In addition, when heat treatment or high-temperature calcination is used to activate the activity of waste cement powder, the energy consumption is relatively high, and greenhouse gas carbon dioxide is released during the treatment process, which is contrary to the current requirements of economy, environmental protection and low energy consumption.

[0003] At the same time, greenhouse gases (such as CO 2 , CH 4 Global climate change caused by excessive emissions of CO 2 To reduce the CO2 emissions during the production process, 2 , strive to achieve domestic carbon emissions peak before 2030 and carbon neutrality before 2060, and the direct CO2 emissions of the global cement industry 2 With emissions increasing by only 4%, the implementation of carbon dioxide capture, storage and utilisation technologies is crucial.

[0004] How to break through the resource recycling of construction waste micropowder and realize CO 2 Large-scale emission reduction and resource utilization, while achieving economic and environmental benefits, is an industry issue that urgently needs to be addressed in the current process of resource utilization in the industry's buildings.

[0005] Patent CN113651549 A discloses a recycled concrete aggregate reinforced with construction waste micropowder and a preparation method. The invention adopts a method of carbonizing the construction waste micropowder after making a reinforced slurry and air-drying it. However, the particle size of the construction waste micropowder ground in this invention is not fine enough, and the activation effect of the construction waste micropowder is limited. In addition, the carbonization is only carried out on the most surface reinforcement layer, the contact area of ​​the reaction is small, and the carbide accounts for only 1%-5%, and the carbonization degree is not high.

[0006] Patent CN106242336 A discloses a method for preparing building mortar using construction waste. The invention obtains construction waste powder by special processes such as screening, grinding, and homogenization, and obtains mortar by external mixing. However, the operation of making construction waste powder in this invention is not detailed enough, and the particle size of the obtained construction waste powder is not fine enough, which has limited activation effect on the activity of the construction waste powder. Summary of the invention

[0007] In view of the defects of the prior art, the purpose of the present invention is to provide a method for carbonizing and reactivating construction waste micropowder, so that the construction waste micropowder can be reused in cement-based materials. The method improves the utilization rate of construction waste, and achieves CO2 reduction while increasing the carbonization degree and enhancing the performance of concrete. 2 Large-scale emission reduction and resource utilization.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for carbonizing and reactivating construction waste micropowder, comprising the following steps:

[0010] (1) Grinding and sieving construction waste powder to obtain 20-25 μm construction waste powder.

[0011] (2) 5-20 parts of the 20-25 μm construction waste powder obtained in step (1) are mixed with 10-40 parts of water, and 0.1-0.2 parts of sodium citrate are added, followed by wet grinding for 20-60 minutes to obtain a 2-5 μm ultrafine construction waste slurry.

[0012] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) is mixed with 0.1-0.3 parts of boric acid and 1-2 parts of polymer electrolyte water reducer and wet-grinded for 6-8 hours, and CO is introduced during the wet-grinding process. 2 After carbonization activation, the carbonized and activated construction waste powder can be used to prepare mortar.

[0013] The parts of the above raw materials are all parts by mass.

[0014] Step (1) specifically comprises: firstly sieving the construction waste powder through a 1.18 mm square sieve, then dry grinding for 15-30 min, and finally sieving to obtain 20-25 μm construction waste powder.

[0015] In step (2), the wet grinding conditions are preferably: the ball-to-material ratio is 1:3, the grinding ball particle size is 1.0-1.2 mm, and the mill speed is 600-800 r / min.

[0016] In step (3), the polymer electrolyte water reducer includes lignin sulfonate water reducer, aminosulfonate water reducer, polycarboxylate water reducer, etc.

[0017] In step (3), CO is introduced 2 The flow rate is preferably 2-3 L / min; the temperature during wet grinding carbonization is preferably controlled at 80-90° C. During the wet grinding carbonization process, samples can be taken every 2 hours to detect whether other substances are generated and whether the reaction is sufficient.

[0018] A method for preparing carbonized construction waste mortar, comprising the following steps: mixing 15-60 parts of carbonized and activated construction waste powder obtained by the above-mentioned construction waste powder carbonization and reactivation method with 80-95 parts of cement, 10-40 parts of water, and 200 parts of fine aggregate, and obtaining carbonized construction waste mortar through vibration, molding, and curing; the parts are all parts by mass. In the preparation method, the fine aggregate is preferably river sand or machine-made sand; the proportion of the mortar is: the content of construction waste powder is 5%-20%, the content of cement is 80%-95%, and the water-cement ratio is 0.4-0.5.

[0019] A carbonized construction waste mortar is obtained by the preparation method of the carbonized construction waste mortar.

[0020] The above-mentioned construction waste micro-powder carbonization reactivation method is applied in the reuse of cement-based materials.

[0021] The main components of waste cement powder are hydrated calcium silicate and calcium hydroxide. The carbonization and reactivation method of construction waste micropowder provided by the present invention is a good innovation to use it as a base material for carbon dioxide absorption and fixation. 2+ After carbonization, CO 2It is sealed in cement-based materials in the form of inorganic carbonates. Studies on pure calcium carbonate powder have shown that calcium carbonate powder has filling, nucleation and dilution effects in cement materials, which can promote the hydration and hardening of cement. Replacing part of cement with calcium carbonate powder can improve the performance of cement and concrete. Combining the carbon dioxide fixation of waste cement powder and the advantages of calcium carbonate in cement hydration, waste cement powder can be treated by accelerating mineral carbonization technology, and the carbonization product can be added to cement for concrete materials, which can improve the mechanical properties and durability of cement-based materials. It can not only improve the utilization rate of construction waste, but also achieve CO 2 permanent and safe storage.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] 1. High-value utilization of solid waste has significant economic and environmental benefits: On the one hand, the present invention rationally uses the solid waste material of construction waste micropowder, which reduces environmental pressure and reduces production costs. On the other hand, the wet grinding carbon fixation process realizes CO 2 Large-scale emission reduction and resource utilization.

[0024] 2. The materials used have good adaptability:

[0025] (1) Beneficial effects of carbonized construction waste micro-powder mortar:

[0026] First, the calcium content in CSH is reduced due to carbonization, which leads to a change in the structure of silica after the silicon dimers are combined with linear chains without cross-linking. Therefore, in the same order of magnitude of CSH gel, calcium carbonate may coexist in nanocrystal size, improving the compressive strength.

[0027] Second, the chemically unstable calcium hydroxide is reduced after carbonization, which accelerates the early strength of the mortar, densifies the surface, and enhances its mechanical properties.

[0028] Third, the calcium oxygen atoms on the surface of calcium carbonate formed after carbonization are arranged in order. During hydration, calcium carbonate forms core points to promote cement hydration, and the growth of hydrated calcium silicate at the core points is rapid and orderly.

[0029] Fourth, after mixing with cement, aluminum phases such as tricalcium aluminate and tetracalcium aluminoferrate will react with calcium carbonate to form unstable hydrated hemi-carbon calcium aluminate, which will gradually transform into stable hydrated mono-carbon calcium aluminate in about 7 days. The formation of calcium aluminate will destroy the original ion balance in the pore solution. The increase in the carbonate ion content in the pore solution will inhibit the reaction of other ions, and the transformation of trisulfide calcium aluminate to monosulfide calcium aluminate will be inhibited. Hydrated calcium aluminate is easy to form and has a larger microscopic volume, which increases the volume of the hydration product, improves the porosity and density, and increases the strength of the concrete.

[0030] (2) Beneficial effects of sodium citrate: On the one hand, the citrate ion has three carboxyl groups and one hydroxyl group. In the slurry, the citrate ion can form a five-membered ring and a six-membered ring complex with the calcium ion, which accelerates the dissolution of calcium ions in the slurry during the wet grinding process, speeding up the dissolution rate of the intermediate minerals and thus speeding up the hydration rate. On the other hand, due to the Ca 2+ and OH - Dissolution makes C 3 The surface of S forms a calcium-deficient silicon-rich layer, Ca 2+ Adsorbed onto the surface of the silicon-rich layer, it carries a positive charge and forms a double electric layer, making C 3 S dissolves Ca 2+ The rate slowed down, while sodium citrate and Ca 2+ The complexation weakens the double electric layer effect, inhibits the formation of the silicon-rich layer, advances the induction period, and accelerates the dissolution.

[0031] (3) Beneficial effects of boric acid: On the one hand, boric acid can react with Ca 2+ By chelating to form a five-membered or six-membered ring structure, Ca 2+ During the wet grinding and carbonization process, the dissolution rate is accelerated. 2+ The complexation weakens the double electric layer effect, inhibits the polymerization of dissolved silica, and thus inhibits the formation of a silicon-rich layer.

[0032] (4) Beneficial effects of polymer electrolyte water reducer: On the one hand, due to the presence of free Ca in the construction waste micropowder slurry 2+ Therefore, the polymer electrolyte water reducer in the alkaline slurry can form a coordination bond with Ca 2+ The polymer electrolyte macromolecules contain these complex-forming groups to form unstable complex polymers, thereby promoting Ca 2+ On the other hand, the alkaline medium of the construction waste micro-powder slurry dissociates the polymer electrolyte into large molecular anions with multiple charges, which form a monomolecular directional adsorption layer on the polar surface of cement particles, with the hydrocarbon chain oriented outward, making the surface of cement particles hydrophobic, thereby reducing the slurry viscosity and breaking through the bottleneck of low solid content of existing carbonization technology.

[0033] 3. Two innovative processes, wet grinding and wet grinding carbonization, are used:

[0034] (1) Beneficial effects of wet grinding: During the wet grinding process, the surface structure of the construction waste micropowder is destroyed due to the mutual extrusion and collision between the construction waste micropowder and the ball, which causes the calcium ions and silicon ions in the construction waste micropowder to dissolve. The particle size of the construction waste micropowder after wet grinding can reach 2-5μm, and its specific surface area is increased and its activity is improved, which can accelerate the later hydration process, generate more CSH gel, and improve the mortar strength.

[0035] (2) Beneficial effects of wet grinding and carbonization simultaneous treatment: During the wet grinding and carbonization simultaneous treatment process, the silicon-rich layer deposited on the surface of the construction waste micropowder can be continuously peeled off, effectively increasing the contact area of ​​the reaction and the CO 2 The carbonization degree of the cement. CSH and calcium hydroxide in the construction waste micro-powder slurry are easily carbonated. The calcite and highly polymerized silica gel formed during the carbonation reaction form a three-dimensional network, which can improve the overall strength of the cement. DETAILED DESCRIPTION

[0036] The present invention is further described in detail below with reference to examples, but the embodiments of the present invention are not limited thereto.

[0037] In the following examples, the construction waste powder used was obtained by grinding waste concrete blocks and had a density of 2600 kg / m 3 , with a specific surface area of ​​300 to 800 m 2 / kg. The cement used is ordinary Portland cement, model P·I 42.5. The polymer electrolyte water reducer used is lignin sulfonate water reducer.

[0038] Example 1

[0039] The preparation of the carbonized construction waste mortar provided in this embodiment comprises the following steps:

[0040] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0041] (2) 5 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 10 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0042] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0043] (4) 15 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 95 parts of cement, 40 parts of water, and 200 parts of river sand, and then vibrated, molded, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0044] Example 2

[0045] The preparation of the carbonized construction waste mortar provided in this embodiment comprises the following steps:

[0046] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0047] (2) 10 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 20 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0048] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0049] (4) 30 parts of the carbonized and activated construction waste slurry of 2-5 μm obtained in step (3) are mixed with 90 parts of cement, 30 parts of water and 200 parts of river sand, and then vibrated, formed and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0050] Example 3

[0051] The preparation of the carbonized construction waste mortar provided in this embodiment includes the following steps: (1) the construction waste powder is first screened through a 1.18 mm square sieve, then dry-ground for 20 minutes, and finally screened to obtain 20-25 μm construction waste powder.

[0052] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0053] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0054] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0055] Example 4

[0056] The preparation of the carbonized construction waste mortar provided in this embodiment comprises the following steps:

[0057] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0058] (2) 20 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 40 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0059] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0060] (4) 60 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 80 parts of cement, 10 parts of water, and 200 parts of river sand, and then vibrated, molded, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0061] Example 5

[0062] The preparation of the carbonized construction waste mortar provided in this embodiment comprises the following steps:

[0063] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0064] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 40 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0065] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2), 0.2 parts of boric acid, and 1.2 parts of polymer electrolyte water reducer were mixed and wet-milled for 6 hours. During the wet-milling process, CO was introduced. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0066] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0067] Example 6

[0068] The preparation of the carbonized construction waste mortar provided in this embodiment comprises the following steps:

[0069] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0070] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 20 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0071] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0072] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0073] Comparative Example 1 (without sodium citrate effect)

[0074] The preparation of the carbonized construction waste mortar provided in this comparative example comprises the following steps:

[0075] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0076] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and wet-milled for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet-milling conditions were as follows: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0077] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0078] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0079] Comparative Example 2 (without boric acid effect)

[0080] The preparation of the carbonized construction waste mortar provided in this comparative example comprises the following steps:

[0081] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0082] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0083] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 1.2 parts of polymer electrolyte water reducer and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0084] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0085] Comparative Example 3 (without the effect of polymer electrolyte water reducing agent)

[0086] The preparation of the carbonized construction waste mortar provided in this comparative example comprises the following steps:

[0087] (1) The construction waste powder is first screened through a 1.18 mm square sieve, then dry ground for 20 min, and finally screened to obtain 20-25 μm construction waste powder.

[0088] (2) 15 parts of the 20-25 μm construction waste powder obtained in step (1) were mixed with 30 parts of water and 0.2 parts of sodium citrate were added, followed by wet grinding for 60 min to obtain a 2-5 μm ultrafine construction waste slurry. The wet grinding conditions were: ball-to-material ratio of 1:3, grinding ball particle size of 1.0-1.2 mm, and mill speed of 800 r / min.

[0089] (3) The 2-5 μm ultrafine construction waste slurry obtained in step (2) was mixed with 0.2 parts of boric acid and wet-milled for 6 hours. CO was introduced during the wet-milling process. 2 The conditions for wet grinding are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2mm, mill speed is 800r / min; CO 2 The flow rate was 2 L / min, and the temperature was controlled at 80 °C during wet grinding and carbonization.

[0090] (4) 45 parts of the 2-5 μm carbonized activated construction waste slurry obtained in step (3) are mixed with 85 parts of cement, 20 parts of water, and 200 parts of river sand, and then vibrated, formed, and cured to obtain carbonized construction waste mortar. The curing conditions are: the temperature is 20±2° C. and the humidity is not less than 95% within 28 days.

[0091] The following Table 1 shows the components and their mass fractions in the above-mentioned Examples 1-6 and Comparative Examples 1-3, and Table 2 shows the performance test results of the carbonized construction waste mortars obtained in the above-mentioned Examples 1-6 and Comparative Examples 1-3.

[0092] Table 1 Components and their mass fractions in Examples 1-6 and Comparative Examples 1-3

[0093]

[0094]

[0095] Table 2 Performance test results of carbonized construction waste mortar obtained in Examples 1-6 and Comparative Examples 1-3

[0096]

[0097] The test methods for the properties in Table 2 are as follows: the fluidity is measured using the GB / T 2419-2005 cement mortar fluidity test method; the setting time is measured using the GB / T 1346-2011 setting time test method; and the compressive strength is measured using a concrete pressure testing machine.

[0098] It can be seen from the above experimental data that the 6 groups of embodiments and 3 groups of comparative examples of the present invention using carbonized construction waste micropowder for reactivation, by changing the wet grinding time and dosage, and controlling sodium citrate, boric acid and polymer electrolyte water reducer respectively, it is found through comparison that the three variables can produce beneficial effects. The carbonized construction waste micropowder mortar prepared by the present invention has better performance than the comparative sample, and has good mechanical properties and durability.

[0099] Although the present invention is disclosed as above with preferred embodiments, it is not intended to limit the scope of the present invention. Any person skilled in the art can make some improvements without departing from the scope of the present invention, that is, all equivalent improvements made according to the present invention should be covered by the scope of the present invention.

Claims

1. A method for carbonizing and reactivating construction waste micropowder, characterized in that: The steps include: (1) Grinding and sieving construction waste powder to obtain 20-25µm construction waste powder; (2) taking 5-20 parts of the 20-25 µm construction waste powder obtained in step (1), mixing it with 10-40 parts of water, adding 0.1-0.2 parts of sodium citrate, and wet grinding it for 20-60 minutes to obtain a 2-5 µm ultrafine construction waste slurry; (3) The 2-5 µm ultrafine construction waste slurry obtained in step (2) is mixed with 0.1-0.3 parts of boric acid and 1-2 parts of polymer electrolyte water reducer and wet-grinded for 6-8 hours. During the wet-grinding process, CO2 is introduced for carbonization activation. The carbonized and activated construction waste powder can be used to prepare mortar; The parts of the above raw materials are all parts by mass.

2. The method for carbonizing and reactivating construction waste powder according to claim 1, characterized in that: Step (1) is: the construction waste powder is firstly screened through a 1.18 mm square sieve, then dry-ground for 15-30 minutes, and finally screened to obtain 20-25 µm construction waste powder.

3. The method for carbonizing and reactivating construction waste powder according to claim 1, characterized in that: In step (2), the wet grinding conditions are: ball-to-material ratio is 1:3, grinding ball particle size is 1.0-1.2 mm, and mill speed is 600-800 r / min.

4. The method for carbonizing and reactivating construction waste powder according to claim 1, characterized in that: In step (3), the polymer electrolyte water reducer includes lignin sulfonate water reducer, aminosulfonate water reducer, and polycarboxylate water reducer.

5. The method for carbonizing and reactivating construction waste powder according to claim 1, characterized in that: In step (3), the flow rate of CO2 is 2-3 L / min; the temperature is controlled at 80-90°C during wet grinding and carbonization.

6. A method for preparing carbonized construction waste mortar, characterized in that: The method comprises the following steps: mixing 15-60 parts of carbonized activated construction waste powder obtained by the method described in any one of claims 1 to 5 with 80-95 parts of cement, 10-40 parts of water and 200 parts of fine aggregate, and obtaining carbonized construction waste mortar through vibration, molding and curing; the parts are all parts by mass.

7. The method for preparing carbonized construction waste mortar according to claim 6, characterized in that: The fine aggregate is river sand or machine-made sand.

8. The method for preparing carbonized construction waste mortar according to claim 6, characterized in that: The mortar has the following proportions: the content of construction waste micro powder is 5%-20%, the content of cement is 80%-95%, and the water-cement ratio is 0.4-0.

5.

9. A carbonized construction waste mortar, characterized in that: Obtained by the method according to any one of claims 6 to 8.

10. Use of the method according to any one of claims 1 to 5 in the recycling of cement-based materials.

Citation Information

Patent Citations

  • Method for preparing building mortar through building rubbish

    CN106242336A

  • Building garbage nanometer crystal nucleus, preparation method and applications thereof

    CN110255957A

  • Recycled aggregate micro-powder concrete, preparation method and drainage road edge stone

    CN112851253A